Functional Trajectories Before and After Major Surgery in Older Adults - Stabenau, Hans F. (Ann Surg, 2018)
OBJECTIVES: We hypothesized that distinct sets of functional trajectories can be identified in the year before and after major surgery, with unique transition probabilities from pre to postsurgical functional trajectories, and that outcomes would be better among participants undergoing elective versus non-elective surgery. BACKGROUND: Major surgery is common and can be highly morbid in older persons. The relationship between the course of disability (ie, functional trajectory) before and after surgery in older adults has not been well-studied for most operations. METHODS: Prospective cohort study of 754 community-living persons 70 years or older. The analytic sample included 250 participants who underwent their first major surgery during the study period. RESULTS: Before surgery, 4 functional trajectories were identified: no disability (n = 60, 24.0%), and mild (n = 84, 33.6%), moderate (n = 73, 29.2%), and severe (n = 33, 13.2%) disability. After surgery, 4 functional trajectories were identified: rapid (n = 39, 15.6%), gradual (n = 76, 30.4%), partial (n = 70, 28.0%), and little (n = 57, 22.8%) improvement. Rapid improvement was seen for n = 31 (51.7%) participants with no disability before surgery, but was uncommon among those with mild disability (n = 8, 9.5%) and was not observed in the moderate and severe trajectory groups. For participants with mild to moderate disability before surgery, gradual improvement (n = 46, 54.8%) and partial improvement (n = 36, 49.3%) were most common. Most participants with severe disability (n = 27, 81.8%) before surgery exhibited little improvement. Outcomes were better for participants undergoing elective versus nonelective surgery. CONCLUSIONS: Functional prognosis in the year after major surgery is highly dependent on premorbid function.